Improving the Students’ Ability in Reading Comprehension on Narrative Text through Keyword Method at the Tenth Grade of SMK Negeri 1 Sogae’adu in 2022/2023 - Laia, Masdefira; Zebua, Elwin Piarawan; Laoli, Adieli; Daeli, Hidayati (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Reading comprehension is the ability of understanding the text, like find the information, messages, or idea from the author. Therefore, it is very important for students to master reading comprehension skills, especially in narrative text. In fact, students at SMK Negeri 1 Sogae'adu experienced problems in understanding narrative text. There were several problems faced by students in reading comprehension: The students were not able to determine the main idea, the students were not able to locate the generic structure of narrative text, the students were not able to recognize or predict the important and unimportant content of the text, and the students were lacked of vocabulary. Concerning these problems, this study aimed to solve students' problems and improve students' ability in reading comprehension through the use of the Keyword Method. This research was carried out using a Classroom Action Research (CAR) design. This research was conducted in two cycles consisting of two meetings in each cycle. There were 4 procedures carried out, namely: Planning, Action, Observation, Reflection. In cycle I, there were 24 students who did not achieved MCC; the average student score was 61.76. The highest score was 87 and the lowest score was 20. Meanwhile, in cycle II, the average score was 87.7, the highest score was 100 and the minimum score was 75, where all students succeeded in achieving the MCC. From the results of this study, it could be concluded that the Keyword Method solves students' problems in reading comprehension and improved students' reading comprehension skills in narrative text.